Hunting primates and managing forests: the case of Iban forest farmers in Indonesian Borneo - Wadley, R.L.; Colfer, C.J.P.; Hood, I.G. (1997)
Hunting by Iban forest farmers in West Kalimantan, Indonesia, is an important part of their subsistence economy, and as such became a focus of study as part of a conservation project in the Danau Sentarum Wildlife Reserve. In this paper, we examine Iban hunting of nonhuman primates with comparison to other large mammals. We analyze rates of encounter and capture, comparing encounters, hunting trips, and animal numbers. Information on habitats hunted shows the importance of secondary and old growth forest. Also examined are Iban attitudes, game preferences, and taboos. The significance of these findings is discussed with regard to the threats to wildlife from increases in the use of shotguns, human population, and habitat destruction, showing that conservation may be aided by promoting or enhancing certain aspects of the traditional Iban agroforestry system.